Awareness of physiotherapy among the Anganwadi workers in Dakshina Kannada: A survey - Tania Johnsey; Narasimman Swaminathan; Sydney Rebello; Kavitha Vishal (Wolters Kluwer Medknow Publications, 2013)
Purpose: The physiotherapist facilitates optimum functional independence, health and well being of the community. An idea of the range of conditions that a physiotherapist can treat will help the community to benefit from their skill. Anganwadi workers (AWW) play a key role in health education and care at the primary care settings especially in rural India. Objectives: The objective of this study was to assess the awareness of physiotherapy among AWW in Dakshina Kannada. Materials and Methods: A cross-sectional survey using a validated questionnaire was conducted among 112 AWW. The data obtained were analyzed and described. Results: Fifty percent of the 112 respondents were not aware of the role of physiotherapy in many of the impairments and only 3% of the AWW were informed during their training period regarding physiotherapy. Conclusion and Implications: Awareness about physiotherapy among the AWWs who participated in the study was poor. Adequate awareness programs among the AWW with regard to physiotherapy, through the various means of information transfer, can be beneficial in helping them to direct the people who are in need of such services.